Using Intergroup Contact Theory to Understand the Practices of Youth-Serving Professionals in the Context of YPAR: Identifying Racialized Adultism. Issue 1 (2nd January 2022) - Kennedy, Heather; Anyon, Yolanda; Engle, Corey; Schofield Clark, Lynn
Abstract: Youth Participatory Action Research (YPAR) is an approach where youth and adults partner to identify and address social issues and, in theory, creates conditions for positive intergroup contact. Yet, little is known about how the practices of YPAR facilitators enable or constrain intergroup contact, particularly in racially diverse groups. Using critical discourse analysis, we examined data from an observational study of YPAR at four sites of a youth organization serving public housing residents to interrogate power dynamics between youth and adults. Our findings suggest that supporting youth in leading and making decisions, encouraging dialogue and using open-ended questions, engaging in joint work, facilitating with intentionality, celebrating accomplishments, and involving staff who are willing to contribute to group activities may enable positive intergroup contact and mitigate adultism. Policing youths' behavior, disengaging with the project, separating adults from youth, and only involving other staff members in punitive discipline are all practices that adults engaged in that constrained intergroup contact. Practices hindering positive intergroup contact may best be understood in relation to racialized adultism. To realize positive intergroup contact in YPAR and other youth-serving settings, therefore, this study suggests that practitioners must mitigate racism and adultism.